Untapped Research Capacities? Mobility and Collaboration at the Intersection of International Development Aid and Global Science Regimes - Fellesson, Måns; Mählck, Paula (International Journal of African Higher Education, 2017)
This article aims to oﬀer some thoughts that go beyond mere bibliometric and scientometric evidence, by empirically and comparatively exploring the conditions for, and the experiences of research and international research collaboration of African PhD holders who graduated with support from development cooperation/aid. The article explores the constraints on research, international research mobility and collaboration, at the intersection of development cooperation and global science regimes. Taking Swedish development cooperation as an example, the article focuses on preconditions and constraints that scholars from Mozambique and Tanzania, in their current positions, experience in their research, with special attention on international mobility and cooperation. Cet article a pour objectif de proposer des réﬂexions qui dépassent les simples preuves bibliométriques et scientométriques, en explorant empiriquement et comparativement les expériences de recherche et de collaborations scientifques internationales de docteurs africains ayant reçu une aide au développement pour leur doctorat. Cet article explore les limites auxquelles se heurtent la recherche, la mobilité internationale et la coopération scientifque internationale, à l’intersection entre la coopération au développement et les programmes scientifques mondiaux. En prenant pour exemple la coopération au développement suédoise, cet article se focalise sur les conditions et les contraintes que les académiques du Mozambique et de Tanzanie, au sein de leur emploi actuel, rencontrent dans le cadre de leur recherche, en portant une attention particulière sur la mobilité internationale et la coopération.